Longitudinal Analysis of Gender Differences in Academic Productivity Among Medical Faculty Across 24 Medical Schools in the United States - Raj, Anita; Carr, Phyllis L; Kaplan, Samantha E; Terrin, Norma; Breeze, Janis L; Freund, Karen M (Academic medicine, 2016)
To examine gender differences in academic productivity, as indicated by publications and federal grant funding acquisition, among a longitudinal cohort of medical faculty from 24 U.S. medical schools, 1995 to 2012-2013. Data for this research were taken from the National Faculty Survey involving a survey with medical faculty recruited from medical schools in 1995, and followed up in 2012-2013. Data included surveys and publication and grant funding databases. Outcomes were number of publications, h-index, and principal investigator on a federal grant in the prior two years. Gender differences were assessed using negative binomial regression models for publication and h-index outcomes, and logistic regression for the grant funding outcome; analyses adjusted for race/ethnicity, rank, specialty area, and years since first academic appointment. Data were available for 1,244 of the 1,275 (98%) subjects eligible for the follow-up study. Men were significantly more likely than women to be married/partnered, have children, and hold the rank of professor (P < .0001). Adjusted regression models documented that women had a lower rate of publication (relative number = 0.71; 95% CI = 0.63, 0.81; P < .0001) and h-index (relative number = 0.81; 95% CI = 0.73, 0.90; P < .0001) relative to men, but there was no gender difference in grant funding. Women faculty acquired federal funding at similar rates as male faculty, yet lagged behind in terms of publications and their impact. Medical academia must consider how to help address ongoing gender disparities in publication records.